Doxycycline and Benznidazole Reduce the Profile of Th1, Th2, and Th17 Chemokines and Chemokine Receptors in Cardiac Tissue from Chronic Trypanosoma cruzi-Infected Dogs - Guilherme de Paula Costa; Laís Roquete Lopes; Maria Cláudia da Silva; Aline Luciano Horta; Washington Martins Pontes; Cristiane M. Milanezi; Paulo Marcos da Mata Guedes; Wanderson Geraldo de Lima; Richard Schulz; João Santana da Silva; Andre Talvani (Hindawi Limited, 2016)
Chemokines (CKs) and chemokine receptors (CKR) promote leukocyte recruitment into cardiac tissue infected by the Trypanosoma cruzi. This study investigated the long-term treatment with subantimicrobial doses of doxycycline (Dox) in association, or not, with benznidazole (Bz) on the expression of CK and CKR in cardiac tissue. Thirty mongrel dogs were infected, or not, with the Berenice-78 strain of T. cruzi and grouped according their treatments: (i) two months after infection, Dox (50 mg/kg) 2x/day for 12 months; (ii) nine months after infection, Bz (3,5 mg/kg) 2x/day for 60 days; (iii) Dox + Bz; and (iv) vehicle. After 14 months of infection, hearts were excised and processed for qPCR analysis of Th1 (CCL2, CCL3, CCL4, CCL5, CXCL9, and CXCL11), Th2 (CCL1, CCL17, CCL24, and CCL26), Th17 (CCL20) CKs, Th1 (CCR5, CCR6, and CXCR3), and Th2/Th17 (CCR3, CCR4, and CCR8) CKR, as well as IL-17. T. cruzi infection increases CCL1, CCL2, CCL4, CCL5, CCL17, CXCL10, and CCR5 expression in the heart. Dox, Bz, or Dox + Bz treatments cause a reversal of CK and CKR and reduce the expression of CCL20, IL-17, CCR6, and CXCR3. Our data reveal an immune modulatory effect of Dox with Bz, during the chronic phase of infection suggesting a promising therapy for cardiac protection.